Massive tumor thrombus in left renal vein and inferior vena cava in renal cell carcinoma on 18-fluorodeoxyglucose positron emission tomography/computerized tomography: “suspension bridge sign” - Zaman, Maseeh; Fatima, Nosheen; Zaman, Areeba; Zaman, Unaiza; Tahseen, Rabia; Zaman, Sidra (World Journal of Nuclear Medicine, 2018)
Tumor thrombosis is a relatively uncommon complication of renal cell carcinoma (RCC), and its diagnosis has therapeutic and prognostic implication. Computerized tomography (CT) is the primary imaging modality for staging RCC, but it has low sensitivity to differentiate between tumor thrombus and bland or benign thrombus. 18-fluorodeoxyglucose positron emission tomography/CT (PET/CT) has a limited role in diagnosis and staging of RCC, but its diagnostic accuracy is considerably high for detection of metabolically active tumor thrombus. We are presenting a case of metastatic left-sided RCC with massive hypermetabolic tumor thrombus extending from left kidney to left renal vein and inferior vena cava giving an interesting “Suspension Bridge” appearance on PET/CT images.
Keywords: 18-fluorodeoxyglucose positron emission tomography/computerized tomography; bland thrombus; massive tumor thrombus; renal cell carcinoma